A laboratory study of liquefaction of partially saturated sand - Arab, A.; Shahrour, I.; Lancelot, L. (Journal of Iberian Geology, 2011)
This experimental study was designed to assess the effects of soil water saturation on the liquefaction of Hostun RF sand. Cyclic undrained triaxial tests were conducted at different soil saturation levels, as given by Skempton’s coefficient, and liquefaction potential curves constructed for each value of this coefficient. Our findings indicate that a lower soil saturation level results in the increased resistance of the sand to liquefaction, in agreement with the tendency observed in other sands. In addition, the variation in sand resistance to liquefaction produced with Skempton’s coefficient was found to be consistent with the semi-empirical relation proposed by Yang et al. (2004).